The winds of war : a novel - Wouk, Herman, 1915- (Boston : Back Bay Books, 2002)
The lives of the members of the Henry family, headed by Naval Commander 'Pug' Henry, are irrevocably changed in the days heading up to the outbreak of World War II.
Adult
Adult
Wilson's Senior High School
Wilson's Fiction
930
Keywords: World War, 1939-1945 -- Fiction; World War, 1939-1945 -- Fiction; War stories; Historical fiction